Emotional intelligence in the portuguese academic context: validation studies of "The Emotional Skills and Competence Questionnaire" (ESCQ) - Luísa Faria (2012)
This study presents the validation of the Emotional Skills and Competence Questionnaire (ESCQ; Taksic, 2000, 2001) in the Portuguese academic context, comparing it with the original Croatian version. It consists of 45 items divided into three subscales - Perceiving and understanding emotion, Expressing and labelling emotion, and Managing and regulating emotion. This self-report measure of emotional intelligence, based on Mayer and Salovey's model, has already been tested in different cultures. It was administered collectively during regular academic hours to a Portuguese sample of 730 students, 381 from high-school and 349 from university. Overall, alpha values were good and similar to those of the original version (>.80), except for managing and regulating emotion (.67). Confirmatory factor analysis was undertaken to verify the factor structure of the ESCQ and revealed that the best fit model has two correlated factors (.55; perception and expression), including only 11 items from the original scale (r(2)> .30). Both sensibility and discriminative power proved to be satisfactory. The ESCQ revealed promising results, but further validation studies with larger samples are needed.